2008
DOI: 10.1159/000114871
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Anti-Inflammatory Potential of <i>Aloe vera</i> Gel (97.5%) in the Ultraviolet Erythema Test

Abstract: Background:Aloe vera is a natural product that is frequently used in soothing skin care products such as aftersun lotions. In the present study we aimed to explore the anti-inflammatory potential of a highly concentrated A. vera gel in the UV erythema test in vivo. Methods: 40 volunteers with skin types II and III were included in the randomized, double-blind, placebo-controlled, phase III monocenter study. Test areas on the back were irradiated with the 1.5-fold minimal erythema dose of UVB. Subsequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 42 publications
0
25
0
7
Order By: Relevance
“…Regarding human models, the effect of Aloe vera is usually studied in skin and epidermis related disorders (Reuter et al, 2008;Vogler and Ernst, 1999). Aloe vera has recently been shown to inhibit inflammatory responses by downregulating MMP-9 in peripheral blood leukocytes (PBLs), and to reduce cytokine (TNF␣ and IL-1␤) production in undifferentiated THP-1 cells and PBLs (Vijayalakshmi et al, 2012;Habeeb et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding human models, the effect of Aloe vera is usually studied in skin and epidermis related disorders (Reuter et al, 2008;Vogler and Ernst, 1999). Aloe vera has recently been shown to inhibit inflammatory responses by downregulating MMP-9 in peripheral blood leukocytes (PBLs), and to reduce cytokine (TNF␣ and IL-1␤) production in undifferentiated THP-1 cells and PBLs (Vijayalakshmi et al, 2012;Habeeb et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6 The herb is used in various conditions like digestive problems, asthma, immune system enhancement, peptic ulcer, externally in skin irritation, burns, scalds, sunburn wounds, eczema, acne, psoriasis, dermatitis, ulcers. 7,8 Aloe Vera also having antidiabetic activity. 9,10 There are established evidences on elevated levels of serum creatinine and urea being reduced by aloe vera in combination with standard antidiabetic drugs.…”
Section: Dangi Et Al Journal Of Chitwan Medical College 2015; 5(14)mentioning
confidence: 99%
“…This plant is used in digestive problems, asthma, peptic ulcer, skin irritation, burns, wound, eczema, acne, psoriasis, dermatitis and diabetes (Puvabanditsin and Vongtongsri, 2005;Reuter et al, 2008;Mohamed, 2011;Yagi et al, 2011). It has been demonstrated that oral administration of mucilage of A. vera to type II diabetes Wistar rat improves the trend of wound healing by increasing in the expression of vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1) which stimulates the fibroblast for reconstruction of extracellular matrix (Atiba et al, 2011;Mirmalek et al, 2015).…”
Section: Aloe Veramentioning
confidence: 99%